Contact Angles of Water‐repellent Porous Media Inferred by Tensiometer‐ TDR Probe Measurement Under Controlled Wetting and Drying Cycles. Issue 6 (27th September 2013) - Subedi, Shaphal; Kawamoto, Ken; Komatsu, Toshiko; Moldrup, Per; Wollesen de Jonge, Lis; Müller, Karin; Clothier, Brent
Abstract : The time dependency of water repellency (WR) in hydrophobic porous media plays a crucial role for water infiltration processes after rainfall and for the long‐term performance of capillary barrier systems. The contact angle (CA) of hydrophobic media normally decreases with continuous contact with water, eventually allowing water imbibition. However, the effect of the reduction in CA with soil‐water contact time on the water retention function of hydrophobic media is not yet fully understood. In this study, water retention characteristics were measured using a hanging water column apparatus equipped with a mini‐time domain reflectometry (TDR) coil probe under controlled wetting and drying in a water‐repellent volcanic ash soil (VAS) and in sands coated with different hydrophobic agents. The contact angle (CA–SWRC ) under imbibition was evaluated based on the inflection points on the water retention curves. For both water‐repellent VAS and hydrophobized sand samples, the calculated CA–SWRC increased with increasing WR. This was determined from both the water drop penetration time and the initial contact angle (CAi ) by the sessile drop method. Calculated CA–SWRC values ranged from 20° to 48° for the water‐repellent VAS and from 40° to 63° for the hydrophobized sand. The CA reduction with contact time was quantified by relating CA–SWRC and CAi . This gave a significant linear relationship for the hydrophobized sand [CA–SWRC = 0.40CAi +11.3 (30° < CAi < 120°), R 2 = 0.66]. A large difference in water‐filled pore distributions under controlled wetting and drying cycles was found on calculating the soil water capacity and pore size density as a function of water potential.